A comparative study of the duties of nominee directors and the liabilities of their nominators: reconciling the law with commercial reality - Yang Chik binti Adam (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2013)
A nominee director is one who is appointed to the board of directors of a company to represent the interests of a particular person or group of shareholders or class of shareholders. Nominee directors are common in the corporate landscape. Section 4, Malaysian Companies Act (CA) 1965 defines 'director' as including “any person occupying the position of director by whatever name called ...”. Under CA 1965 there is no specific definition on nominee director. By virtue of the Malaysian Companies Amendment Act 2007, s.132 (1E) clarifies statutorily the responsibility of nominee director, 'a director who was appointed by virtue of his position as an employee of a company or who was appointed by or as a representative of a shareholder, employer or debenture holder ...”. The nominee directorship is an issue peculiar by reason of their dual loyalty. This dual loyalty creates the difficulty such as the extent to which the nominee director may act in the interest of the nominator and disclose information to his or her nominator or the degree of involvement of the nominee director in the running of the company. This provision is silent on the liability of the nominator. It is recommended that s.132(1E) CA 1965 be reviewed so as to balance accountability and efficiency arguments. The research adopted the doctrinal analysis of data from both primary and secondary sources of law from Australia, United Kingdom and Malaysia. Semi-structured interviews were conducted with the relevant informants from the corporate industry. In reviewing s.132(1E) CA 196 the research revealed, inter alia, that s.187Australian Corporations Act 2001 may be adopted because little modifications are required but it would only be applicable in a wholly-owned subsidiary. The result of the interviews indicated that there is some uncertainty as to who nominee directors are despite commonly found. The informants indicated that s.132(1E) CA 1965 is clear. In the event of conflict of interests the company's interests prevail over the nominator. The informants were also uncertain on the issue of whether to hold the nominator liable for the acts of the nominee director. The extra legal solutions based on the Islamic law framework vide the Directors' Islamic Code of Ethics reveals a moral code of behaviour has the potential to be advanced to modern corporations.